The Multicultural Personality Inventory – Short Form: Development and Validation. (2nd July 2020) - Fietzer, Alexander W.; Black, Natasha; Ponterotto, Joseph G.; Magaldi, Danielle; Lipari, Kristen; Pratt, Andrea; Dillon, Gary L.
Abstract: We report the development and validation of the Multicultural Personality Inventory – Short Form (MPI-SF). Results supported the correlated seven-factor model with a sample of 333 college students. Scores from MPI-SF factors were internally consistent, temporally stable over a one- and two-month period, and predicted variance in college adjustment consistent with multicultural personality theory.